Geographical Environment аnd Society Development - Dina Jurevna Fedjunina (Наука. Инновации. Технологии)
The dialectics of the nature and society always and everywhere has mutual character. As the nature continuously and constantly influences society, and society continuously and constantly influences the nature. There are the various directions concerning influence of the environment on the person in which often is absolutized either one, or other party of dialectic unity.